Local dynamics in an era of globalization 21st century catalysts for development - Yusuf, Sahid (Ed.); World Bank; Evenett, Simon (Ed.); Weiping Wu (Ed.) (Oxford Oxford University Press, 2000)
Local Dynamics in a era of globalisation is a collection of papers by leading authorities discussing some of the major aspect of decentralization and urban change in the context of globalization. This volume will be of special interest to Governments, Non
Keywords: Economic development; Globalization; Urbanization; Decentralization in government